Chorionic villus sampling and the risk of hypertensive disorders of pregnancy. (16th November 2010) - Khalil, A; Memtsa, M; Kaler, MS; Pandya, P
Abstract : Background: There is conflicting evidence about whether chorionic villus sampling (CVS) increases the risk of hypertensive disorders of pregnancy (HTD). Our aim was to ascertain whether CVS affects the risk of developing HTD. Methods: This is an ongoing study, both retrospective and prospective. The authors present here the retrospective analysis of data from 2000 to 2009. The authors retrieved the pregnancy outcomes of all women who had CVS at the University College Hospital Fetal Medicine Unit between 11+0 and 13+6 weeks' gestation. Exclusion criteria included subsequent termination or spontaneous abortion; abnormal fetal karyotype; pre-existing risk factors for preeclampsia, such as chronic hypertension and renal disease. The authors also randomly selected controls from women who booked and delivered at UCH. Multiple logistic regression analysis was used to identify and adjust for potential confounding factors. Results: The authors identified 258 women who had CVS and 1036 controls. Of 258 who had CVS, 20 (7.7%) subsequently developed HTD (9 (3.5%) PE (2 early onset before 34 weeks, 7 late onset) and 11 (4.3%) pregnancy induced hypertension (PIH)). Of the 1036 controls, 39 (3.8%) subsequently developed HTD (26 (2.5%) PE (6 early onset, 20 late onset) and 8 (0.8%) PIH). Compared with controls, women who had a CVS were significantly more likely subsequently to develop HTD (p<0.001). Conclusion: CVS is associated with an increased risk of HTD. Placental disruption caused by needle insertion may alter the balance of proangiogenic factors and antiangiogenic factors, such as sFlt-1 and PlGF. Alternatively, placental disruption may cause an inflammatory reaction leading to the release of some factor(s) into the maternal circulation which may trigger HTD.